2012
DOI: 10.1161/hypertensionaha.111.189605
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Are Able to Synthesize and Release Catecholamines Both In Vitro and In Vivo

Abstract: Abstract-Recently it has been demonstrated that catecholamines are produced and used by macrophages and mediate immune response. The aim of this study is to verify whether endothelial cells (ECs), which are of myeloid origin, can produce catecholamines. We demonstrated that genes coding for tyrosine hydroxylase, Dopa decarboxylase, dopamine ␤ hydroxylase (D␤H), and phenylethanolamine-N-methyl transferase, enzymes involved in the synthesis of catecholamines, are all expressed in basal conditions in bovine aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 56 publications
(46 reference statements)
5
70
0
Order By: Relevance
“…In addition, CAs are known to be elevated in response to vascular injury and to contribute to arteriogenesis and neoangiogenesis in response to hindlimb ischemia, possibly via increased vascular endothelial growth factor production induced by activation of the EC membrane-residing ␤ 2 ARs (as the same authors had shown previously 8 and again in this study 7 ). Thus, it appears that this capability of ECs to produce and release their own CAs serves primarily as a homeostatic, self-protective mech-anism to defend the cell against vascular injury/stress and ischemia (Figure).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In addition, CAs are known to be elevated in response to vascular injury and to contribute to arteriogenesis and neoangiogenesis in response to hindlimb ischemia, possibly via increased vascular endothelial growth factor production induced by activation of the EC membrane-residing ␤ 2 ARs (as the same authors had shown previously 8 and again in this study 7 ). Thus, it appears that this capability of ECs to produce and release their own CAs serves primarily as a homeostatic, self-protective mech-anism to defend the cell against vascular injury/stress and ischemia (Figure).…”
supporting
confidence: 79%
“…Macrophages, for instance, not only respond to CAs but can also produce them, essentially operating an autocrine feedback loop in which CAs produced and released by the macrophage activate ARs on the surface of the very same macrophage to regulate production of the key proinflammatory cytokine interleukin 1␤. 6 Now, ECs have been added to this expanding list: in a very interesting and elegant study reported in this issue of Hypertension, Sorriento et al 7 found that such an autocrine feedback system of CAs is present also in ECs regulating their function ( Figure). Working with bovine aorta-derived ECs in culture, the authors found surprisingly that ECs express naturally all the enzymes of the entire CA biosynthetic pathway, from tyrosine hydroxylase all the way down to phenylethanolamine N-methyl transferase, are capable of synthesizing all 3 natural CAs and of releasing (at least) NE and Epi into their extracellular environment, and, finally, are also capable of metabolizing NE and Epi because they also express catechol-O-methyl-transferase and monoamine oxidase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Of course, this model represents a streamlined point of view of the whole story because adrenal gland is not the exclusive site of production of catecholamines. 6 Likewise, the same group had previously 2 shown that turning down via a gene therapy approach the adrenal levels of GRK2, a master regulator of cardiac βAR desensitization alongside with β-arrestins, 3 cardiac function after myocardial infarction was substantially improved. Ergo, modulation of βAR signaling via β-arrestin-1 and GRK2 inhibition from both the heart and the adrenal (Figure) seems to lead to a reduced neurohumoral burden, halting the myocardial adverse remodeling and increasing the inotropic reserves.…”
Section: See Related Article P 404-412mentioning
confidence: 97%
“…Supporting a potential role for β-arrestin-1 in the regulation of these activities, β 2 AR has been shown recently to partake in all the above-mentioned processes. 6,8,9 Equally important, growing evidence indicates that loss or dysfunction of β-arrestin-2 results in profound disturbance of insulin …”
Section: See Related Article P 404-412mentioning
confidence: 99%